Establishment of Standard Methods for the Measurement of Eye-Hand Visual-Motor Reaction Time. - Willms, Amy E.; Dalton, Kristine N.; Reich, Kimberly (Optometry & Visual Performance, 2017)
Background: Eye-hand visual-motor reaction time (EH-VMRT) is critical for sports performance. However, there are no validated standardized methods available for determining baseline EH-VMRTs or for training EH-VMRT. This study validated methods for assessing baseline EH-VMRT and implementing training programs using the Sports Vision Trainer (SVT, Australia). Methods: Proactive, Go/NoGo, and Reactive protocols were evaluated. Each protocol was examined using central and peripheral EH-VMRT tasks. Participants completed 10 trials of each task. The Proactive protocol was used to determine the number of trials needed to measure a baseline EH-VMRT. The relationship between stimulus duration (relative to baseline EH-VMRT) and response accuracy were examined for Go/NoGo and Reactive training protocols. Results: Significant overall concordance was found for EH-VMRT across trials for central (ρco = 0.694) and peripheral (ρco = 0.858) tests. Session mean EH-VMRT was strongly concordant with the mean of the first three trials of the central (ρc = 0.908) task and the mean of the first 2 trials of the peripheral (ρc = 0.937) task. Moderate accuracy (75%) was achieved on Go/NoGo protocols when the stimulus duration was increased by 45 ms (central) and 94 ms (peripheral) relative to the baseline EH-VMRTs. Moderate accuracy was attained on Reactive protocols by adding 40 ms (central) and 59 ms (peripheral) to the baseline EHVMRTs. Conclusion: Representative baseline EH-VMRTs can be obtained within two to three trial runs for central and peripheral tasks. Implementation of Go/NoGo training programs require longer stimulus durations relative to baseline (70 ms) than Reactive training programs (50 ms) to achieve moderate accuracy, which suggests that Go/NoGo protocols may be more difficult than Reactive protocols. These methods should be used in the development of future sports vision training programs.